2017
DOI: 10.1186/s12884-017-1474-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric professionals’ perceptions of non-invasive prenatal testing for Down syndrome: clinical usefulness compared with existing tests and ethical implications

Abstract: BackgroundWhile non-invasive prenatal testing (NIPT) for fetal aneuploidy is commercially available in many countries, little is known about how obstetric professionals in non-Western populations perceive the clinical usefulness of NIPT in comparison with existing first-trimester combined screening (FTS) for Down syndrome (DS) or invasive prenatal diagnosis (IPD), or perceptions of their ethical concerns arising from the use of NIPT.MethodsA cross-sectional survey among 327 obstetric professionals (237 midwive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…This is in keeping with previous findings where even within a group of only USA-based MFM Fellows, the accuracy of a MFM fellow’s knowledge regarding possible indications for cfDNA screening trended towards higher levels with increasing year in the MFM fellowship [ 20 ]. As a whole, the majority of our Canadian participants demonstrated support towards use of cfDNA screening, a similar finding to attitudes of healthcare providers found in other countries like the USA, United Kingdom, Netherlands, and China [ 11 , 20 22 ]. However, we discovered that MFM and OB/GYN demonstrated significantly more support towards the use of cfDNA screening than GP and MW.…”
Section: Discussionsupporting
confidence: 81%
“…This is in keeping with previous findings where even within a group of only USA-based MFM Fellows, the accuracy of a MFM fellow’s knowledge regarding possible indications for cfDNA screening trended towards higher levels with increasing year in the MFM fellowship [ 20 ]. As a whole, the majority of our Canadian participants demonstrated support towards use of cfDNA screening, a similar finding to attitudes of healthcare providers found in other countries like the USA, United Kingdom, Netherlands, and China [ 11 , 20 22 ]. However, we discovered that MFM and OB/GYN demonstrated significantly more support towards the use of cfDNA screening than GP and MW.…”
Section: Discussionsupporting
confidence: 81%
“…22 Studies have found that obstetricians had more certain views about the usefulness of NIPT than midwives had. 23 To consider this potential bias, a questionnaire to the healthcare providers would be useful for understanding their perceptions, attitudes, and the extent of any bias towards NIPT or invasive diagnostic procedures. Standardised counselling materials (interview scripts, booklets, videos, question and answer information sheets) distributed to women may also minimise dynamic human factors during the counselling session.…”
Section: Discussionmentioning
confidence: 99%
“…Using a sequential explanatory mixed-methods design [ 27 ], the first phase of a cross-sectional survey among DS screening providers assessed knowledge, attitudes and clinical experiences of NIPT compared to conventional screening and diagnosis. One of the significant findings was that obstetric providers in public sectors reported significantly more ethical concerns in the clinical implementation of NIPT than private providers, including women’s informed decision making, lack of consultation, unequal access to NIPT, and unnecessary use of resource (e.g., multiple DS screening tests) [ 18 ]. The finding addressed the importance of addressing system-level interventions in facilitating informed choice for reproductive autonomy, effective coordination between public and private sectors, and fairer resource allocation for better DS screening techniques, including an option of introducing NIPT in public antenatal care settings.…”
Section: Methodsmentioning
confidence: 99%